Knowledge Discovery in Nanophotonics Using Geometric Deep Learning. (19th December 2019) - Kiarashinejad, Yashar; Zandehshahvar, Mohammadreza; Abdollahramezani, Sajjad; Hemmatyar, Omid; Pourabolghasem, Reza; Adibi, Ali
Abstract : Herein, a new approach for using the intelligence aspects of artificial intelligence for knowledge discovery rather than device optimization in electromagnetic (EM) nanostructures is presented. This approach uses training data obtained through full‐wave EM simulations of a series of nanostructures to train geometric deep learning algorithms to assess the range of feasible responses as well as the feasibility of a desired response from a class of EM nanostructures. To facilitate the knowledge discovery, this approach combines the dimensionality reduction technique with convex‐hull and one‐class support‐vector‐machine (SVM) algorithms to find the range of the feasible responses in the latent response space of the EM nanostructure. More importantly, the one‐class SVM algorithm can be trained to provide the degree of feasibility of a response from a given nanostructure. This important information can be used to modify the initial structure to an alternative one that can enable an initially unfeasible response. To show the applicability of this approach, it is applied to two important classes of binary metasurfaces (MSs), formed by an array of plasmonic nanostructures, and periodic MSs formed by an array of dielectric nanopillars. These theoretical and experimental results confirm the unique features of this approach for knowledge discovery in EM nanostructures. Abstract : Knowing the feasibility of achieving a desired response from an electromagnetic nanostructure before attempting any design effort is very helpful in avoiding suboptimum results or even convergence issues. Herein, a geometric deep learning platform learns the underlying physics of a given class of nanostructures and uses this knowledge to reveal the realm of responses those nanostructures are capable of offering.